Environmental hazards : assessing risk and reducing risaster - Smith, Keith, 1938- (Routledge, 2013)
The much expanded sixth edition of Environmental Hazards provides a fully up-to-date overview of all the extreme events that threaten people and what they value in the 21st century. It integrates cutting-edge material from the physical and social sciences to illustrate how natural and human systems interact to place communities of all sizes, and at all stages of economic development, at risk. It also explains in detail the various measures available to reduce the ongoing losses to life and property. Part One of this established textbook defines basic concepts of hazard, risk, vulnera.